Doxorubicin chemotherapy for presumptive cardiac hemangiosarcoma in dogs†. (18th December 2014) - Mullin, C.M.; Arkans, M.A.; Sammarco, C.D.; Vail, D.M.; Britton, B.M.; Vickery, K.R.; Risbon, R.E.; Lachowicz, J.; Burgess, K.E.; Manley, C.A.; Clifford, C.A.
Abstract: Sixty‐four dogs were treated with single‐agent doxorubicin (DOX) for presumptive cardiac hemangiosarcoma (cHSA). The objective response rate (CR + PR) was 41%, and the biologic response rate (CR + PR + SD), or clinical benefit, was 68%. The median progression‐free survival (PFS) for treated dogs was 66 days. The median survival time (MST) for this group was 116 days and was significantly improved compared to a MST of 12 days for untreated control dogs ( P  = 0.0001). Biologic response was significantly associated with improved PFS ( P  < 0.0001) and OS ( P  < 0.0001). Univariate analysis identified larger tumour size as a variable negatively associated with PFS. The high rate of clinical benefit and improved MST suggest that DOX has activity in canine cHSA.